The Rural Scene in the Short Stories of Jamila Hashmi - Khan, Nasir Iqbal; Kanwal, Rukhsar; Siddique (Makhz (Research Journal), 2025)
Jamila Hashmi is a renowned fiction writer of Urdu literature. She has gained immense popularity in short stories and novels. In her novels, she has left an impression of individuality that Urdu literary circles can never forget. Taking advantage of the vast canvas of the novel, she has beautifully highlighted various aspects of society, in which the supremacy of men over women comes to the fore as an important aspect. Several novels by Jamila Hashmi have come to the fore. Her social novels include “Talaash-e-Baharan”, “Jog Ki Raat”, “Aatsh-e-Rafta” and “Rohi”. “Talaash-e-Baharan” is her best novel. She has also been awarded the Adamji Award for it. It was first published in June 1961 by Urdu Academy Sindh, Karachi. Along with social novels, Jamila Hashmi has also written two successful historical novels titled "Face to Face" and "Dasht Sous". Jamila Hashmi has three collections of short stories, including "Aap Beti Jag Beti", "Apna Apna Jahannam" and "Rang-e-Bhoom". This article is discussed about her short stories.